Pediatric Renal Transplantation in a Highly Sensitised Child—8 Years On. (26th January 2012) - Quinlan, Catherine; Awan, Atif; Gill, Denis; Waldron, Mary; Little, Dilly; Hickey, David; Conlon, Peter; Keogan, Mary
Abstract : Highly sensitised children have markedly reduced chances of receiving a successful deceased donor renal transplant, increased risk of rejection, and decreased graft survival. There is limited experience with the long-term followup of children who have undergone desensitization. Following 2 failed transplants, our patient was highly sensitised. She had some immunological response to intravenous immunoglobulin (IVIg) but this was not sustained. We developed a protocol involving sequential therapies with rituximab, IVIg, and plasma exchange. Immunosuppressant therapy at transplantation consisted of basiliximab, tacrolimus, mycophenolate mofetil, and steroids. At the time of transplantation, historical crossmatch was ignored. Current CDC crossmatch was negative, but T and B cell flow crossmatch was positive, due to donor-specific HLA Class I antibodies. Further plasma exchange and immunoglobulin therapy were given pre- and postoperatively. Our patient received a deceased donor-kidney-bearing HLA antigens to which she originally had antibodies, which would have precluded transplant. The graft kidney continues to function well 8 years posttransplant.